Human factors and project challenges influencing employee engagement in a project-based organisation (PBO). Issue 4 (16th April 2018) - Matthews, Judy; Stanley, Tracy; Davidson, Paul
Abstract : Purpose: The purpose of this paper is to provide insights into the project challenges, human factors and knowledge development that influence the nature of employee engagement in a project team within a global project-based organisation. Design/methodology/approach: A qualitative research design used semi-structured interviews, and observations in team meetings and the work environment to identify characteristics in the work environment which influenced employee engagement. Findings: Workplace characteristics that influence employee engagement relate to the project challenges, the problem-solving nature of work, and achieving specified outcomes within time allocations. Human factors including the manager's behaviours with feedback and recognition of effort, mentoring, and encouraging collaboration are important in team environment. The potential for learning and knowledge development from the project and with the team positively influence engagement. Research limitations/implications: This study examines the characteristics of an established project team of 13 consultant engineers from eight nationalities, and forms a basis for future comparison with other project teams with different job types and demographic profiles. Practical implications: This study contributes to project management (PM) research by broadening the focus from human factors influencing employee engagement to project challenges and knowledge development, with implications for managers in project-based organisations in terms of job design, development of team climate, team processes and their own behaviours. Originality/value: This study contributes to human factors in PM literature through exploratory research into the antecedents of employee engagement.